Sistema de monitoramento de processos judiciais e controle de prazos utilizando JavaScript, Node.js e a API Escavador - Martins, Thiago Angelo (2022)
Lawsuits migration to electronic environments associated with a bigger demand for productivity at Law offices has caused a need for new methods of resolution of problems for the job related activities, as an example, the deadlines management and the lawsuits monitoring. Both public and private departments have invested on technological solutions wich attempt to facilitate mentioned activities, through softwares that control precisely the lawsuits deadlines and unify follow-ups, wich before were monitored in each court website. This paper has the objective to propose an automatation tool for the Law operator workflow, easing repetitives and daily activities, through the development of an web application that uses JavaScript and Node.js, using Brazil's courts data coming from the judicial API Escavador. This paper main contribution is to show a web application functional prototype for the lawsuits monitoring and deadlines management consuming data from Brazil's courts through the judicial Escavador API.